Variation Of Moisture Content And Specific Gravity of Two Sago Species - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRACT Two sago species under study, namely Metroxylon rumphii Mart. and Metroxylon sagus Rottb. are found abundantly in eastern part of Indonesia. Those two sago species are mainly exploited for food production and there is still no effort to utilize the outer part of the sago stem which is left in the sago forest. Study on sago wood moisture content and specific gravity consists of initial and maximum moisture content, basic and air dry specific gravity. ISO standard was employed in the research. Initial and maximum moisture content of two sago species show a significant increasing trend from butt to lop. There is no difference between the two sago species. On the other hand, basic wood specific gravity displays a different result compared to air dry wood. Both measures are influenced significantly by position along the trunk, but the two sago species express different air dry wood specific gravity. ABSTRAK Dua spesies sagu yang diteliti yaitu Metroxylon rumphii Mart. clan Metroxylon sagus Rottb., dijumpai sangat melimpah di Indonesia bagian timur. Kedua spesies sagu hanya diambil tepung sagunya untuk makanan rakyat dan belum ada usaha untuk mengolah kayu sagu yang ditinggal di hutan. Penelitian ini meliputi kadar air inisial dan maksimum serta berat jenis kayu kering angin dan basah. Keempat sifat fisika kayu ini sangat periling untuk menentukan kemasupan kayu sagu bagi pengolahan selanjutnya. Prosedur ISO digunakan dalam penelitian ini. Kadar air inisial dan maksimum kedua spesies sagu menunjukkan kenaikan dart pangkal ke ujung. Kedua spesies tidak berbeda nyata. Di lain pihak beret jenis kayu basah berbeda nyata terhadap berat jenis kering angin. Keduanya dipengaruhi oleh posisi longitudinal, tetapi kedua spesies mempunyai berat jenis kering angin yang berbeda.